Politik Aksi Humaniter Organisasi Kemanusiaan Dalam Menangani Imigran Ilegal Tahun 2016 (Studi Kasus IOM dan UNHCR di Surabaya) - Made Selly Dwi Suryanti (Politicos: Jurnal Politik Dan Pemerintahan, 2021)
This paper aims to observe the principles of humanitarianism in the current era. The principle of humanitarianism which consists of humanity, neutrality, impartiality and independence tends to be ignored. The neglect is based on the interests carried by each humanitarian organization. Therefore, the principle tends to be mixed with political affairs. This practice can be seen from the two humanitarian organizations IOM and UNHCR in carrying out their role in dealing with illegal immigrants, especially at the Immigration Detention Center, Surabaya. In practice the element of importance is given priority, giving rise to a dilemma for both organizations in carrying out their mandate as a humanitarian organization. These dilemmas include limited resources, internal work relations patterns of personnel, humanitarian worker’s motivation. Because of the dilemma, it is almost difficult for both organizations to adopt the principle of humanitarianism. In the end, combining elements of interest becomes a new term in humanitarian action. The term is known as new humanitarianism. This writing uses qualitative research methods with primary and secondary data sources. Primary data taken through interviews, observations and secondary data sources taken through books, journals, online news, government regulations. The discussion of this paper will use several concepts, namely humanitarianism and new humanitarianism.